1990
DOI: 10.1177/0148607190014002143
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic therapy of catheter infections in patients receiving home parenteral nutrition

Abstract: Fifty-eight episodes of catheter-related sepsis in 21 patients receiving home parenteral nutrition were retrospectively studied. Of 81 organisms isolated from the blood, 59% were Gram-positive cocci, 25% were Gram-negative bacilli, and 16% were yeast. Attempts to treat bacterial infections at home with antibiotic therapy while the catheter remained in place were made; fungal isolation resulted in immediate hospitalization and catheter removal. Gram-negative infections more often resulted in eventual hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…29,37 The prevalence of fungal infections was low in our cohort of patients similar to that reported in several studies. 13,38 This study is unique in that our cohort is one of the largest evaluations of CA-BSI in children on HPN in the acute posthospital phase. Although retrospective, our findings suggest that the elevated rates of CA-BSI may be reduced by interventions focused on the immediate hospital discharge period with reinforcement provided before the sixth month of HPN receipt.…”
Section: Discussionmentioning
confidence: 99%
“…29,37 The prevalence of fungal infections was low in our cohort of patients similar to that reported in several studies. 13,38 This study is unique in that our cohort is one of the largest evaluations of CA-BSI in children on HPN in the acute posthospital phase. Although retrospective, our findings suggest that the elevated rates of CA-BSI may be reduced by interventions focused on the immediate hospital discharge period with reinforcement provided before the sixth month of HPN receipt.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the 28 included studies were conducted in Europe ( n = 21) ( 15 , 16 , 24 , 31–34 , 36–39 , 41–45 , 48 , 50–53 ) and the United States ( n = 6) ( 17 , 35 , 40 , 46 , 47 , 54 ) ( Supplemental Figure 2 ). Twenty-five studies were carried out in tertiary hospitals and/or specialized IF units ( 15–17 , 24 , 33–35 , 37–54 ) and 2 studies were multicenter ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies defined CRBSIs according to the CDC ( 17 , 35 , 39 , 43–45 , 52 ) or IDSA ( 15 , 16 , 31 , 32 , 36 , 50 ) guidelines; the other studies used either nonstandard definitions or did not report the definition used ( 33 , 34 , 37 , 41 , 48 , 49 , 51 , 53 , 54 ). Two studies reported a slightly modified definition, but were still considered as appropriate and were counted as using the CDC definition ( 24 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However multiple complications can arise from the use of these catheters, the most com mon and feared being an infection of the cath eter itself potentially leading to life-threaten ing catheter sepsis [3,8], Until recently, since a complete chemotherapeutic restitution of in fected polymer was considered impossible, the treatment of choice was the removal of the contaminated catheter [5,8]. Lately, however, attempts have been made more and more fre quently to maintain the last available central venous line of severely ill patients with anti biotics [9][10][11][12], This manner of treatment is rather controversial and many ambiguities re main concerning appropriate modes of treat ment to eliminate the various bacteria which can cause catheter infection [10,12]. Until now, gram-positive agents such as Staphylococcus epidermidis and Staphylococcus aureus have been considered as the primary cause of this infectious complication [4,13,14], Hence, sci entific interest has focused mainly on both these causative agents.…”
Section: Introductionmentioning
confidence: 99%